1971
DOI: 10.1038/bjc.1971.80
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Significance of Prognostic Factors in Breast Carcinoma

Abstract: SUMMARY.-A retrospective detailed study of 272 cases of breast carcinoma treated by radical mastectomy was published by Hamlin (1968). An (McWhirter, 1957), delay (Registrar General, 1967), clinical stage (Paterson, Tod and Russell, 1939), axillary node involvement (Myers, Axtell and Zelen, 1966), size of axillary nodes (Fisher, Slack and Bross, 1969), internal mammary node involvement (Handley and Thackray, 1954), malignancy grading of tumour (Bloom, 1950), host response (Hamlin, 1968), hormone balance (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
28
0
3

Year Published

1974
1974
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 6 publications
3
28
0
3
Order By: Relevance
“…This may also help to explain some of the apparently contradictory findings in the literature. Reports published since 1970 that have shown no significant relationship between delay and survival have generally been confined to patients with early stage (operable) disease (Alderson et al, 1971;Dennis et al, 1975;Wallgren et al, 1976;Fisher et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…This may also help to explain some of the apparently contradictory findings in the literature. Reports published since 1970 that have shown no significant relationship between delay and survival have generally been confined to patients with early stage (operable) disease (Alderson et al, 1971;Dennis et al, 1975;Wallgren et al, 1976;Fisher et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The significance of lymphoplasmacytic reaction has been debated for many years (Cutler et al, 1969;Alderson et al, 1971;Rosen et al, 1981a;Dawson et al, 1982). Although considered by many to be an expression of host defence reaction and, therefore, indicative of a favourable prognosis, this has not been confirmed by others.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to the investigation of the relationship of fibrocystic disease to cancer has been to determine the incidence of the former in biopsies of patients whose breasts have been subsequently removed for carcinoma. Results 2.5% of 1200 patients with breast cancer had a previous biopsy revealing benign disease, whereas only 1.1 % of 120 patients with cancer elsewhere had a previous breast biopsy which revealed benign disease. Black and associatesz2 reviewed the breast biopsies obtained years previously from 93 patients with cancer, and found that an appreciable number had in situ cancer or "precancerous mastopathy," although the original diagnosis rendered was only that of fibrocystic disease.…”
mentioning
confidence: 97%